Notes on Scottish Bronze Rapiers, on an Incense-cup from Kirkcudbrightshire, and a Bronze Chisel from Dumfriesshire - Corrie, John M (Proceedings of the Society of Antiquaries of Scotland, 1928)
A review of rapier-daggers and rapier-swords with particular reference to a group of twelve from Drumcoltran. All other examples are isolated finds. An incense-cup was found in a mound along with cremated human bone. A flanged chisel is of unknown provenance.